RBP2GO 2.0: integrating disease associations and sequence features to explore RNA-binding protein functions - Cantarella, Simona; Neffe, Jule; Hermes, Malte; Rauscher, Fabio; Schwarz, Robert; Jaisankar, Praarthanaa; Schäfer, Enno; Caudron-Herger, Maïwen (Nucleic acids research, 2026)
RNA-binding proteins (RBPs) play key roles in a wide range of biological processes and human diseases. Here, we updated RBP2GO, a comprehensive resource on RBPs, their binding partners, and functions across 13 species. The database RBP2GO 2.0 now provides additional information on disease ontology to better relate RBP functions to their impact in human diseases. It also integrates knowledge from new proteome-wide RBP studies and provides specific information on sequence features through intuitive cartoon-style representations, such as associated RNA-binding peptides, when available. Existing eCLIP/iCLIP datasets from ENCODE have been linked to the corresponding proteins, along with RNA dependence information from the R-DeeP database. Protein characterization is further supported by two scores, the RBP2GO Score and the RBP2GO Composite Score, which reflect the probability that the protein binds to RNA. The scores are now visualized using violin plot distributions for the whole proteome of each species. The redesigned user interface enables intuitive searches for protein names, gene ontology terms, disease ontology terms, and protein domains directly from the Home page and provides extended, versatile search options via the Advanced Search module. RBP2GO 2.0 serves as a valuable tool for investigating new RBP functions and is publicly accessible at https://RBP2GOv2.dkfz.de.
Veröffentlicht: 24. November 2025
Gesehen am 23.01.2026